Seeing is Believing but is Hearing? Comparing Audio and Video Communication for Young Children - Tarasuik, Joanne C.; Kaufman, Jordy; Galligan, Roslyn (Frontiers in Psychology, 2013)
Video communication has been shown to create a sense of proximity between young children and parents. To determine if video affords a stronger sense of proximity and engagement than a traditional telephone, the current experiment employed a Separation and Reunion Paradigm with either a video-link or an audio-link available to the separated dyad. Results revealed that during the separation with a video-link, more children remained content to be physically alone than during the audio-link, children played more and displayed more positive affect. This is the first empirical demonstration that video provides a stronger sense of proximity and enjoyment for young children than audio, suggesting that video is a more appropriate medium to meaningfully connect children to relatives during geographical separation.